Red leaves eaudiobook - Cook, Thomas H. (Recorded Books Inc., 2006)
In Red Leaves, Edgar Award-winning author Thomas H. Cook pens a compelling tale of suspicion and its corrosive effects on a family. When a little girl is missing on the morning after his teenaged son baby-sits for her, Eric Moore watches his world crumble as suspicion falls on his son. Although Eric hires a lawyer to prepare his son's defense, a haunting thought slithers into his mind. What if he has been nurturing a monstrous fiend?